Kajian Yuridis Terhadap Pertanggungjawaban Pidana Pelaku Tindak Pidana Korupsi - Jefta Ramschie; Reimon Supusepa; Yanti Amelia Lewerissa (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The improvement of society's social life, science and technology, has resulted in the growing of criminal acts. Purposes of the Research: The aim of this study is to analyze the criminal liability of the corruption perpetrators and the judges considerations in deciding the case. Methods of the Research: The type of research that used is "Juridicial Normative" research, which is descriptive analysis, statute approaches, Case Approaches, Conceptual Approaches. The technique of collecting law materials is through literature study, then the analysis of Law is qualitative.Results of the Research: The result of the research showed that The Judges of Ambon District Court, sentenced LI as the Head of Ambon City Environment and Waste. The primary consideration in imposing a criminal offense using Article 2 verse (1) is the End Year bonus payment started from 2019-2020. Therefore the Judges conclude that none of the elements of Article 2 verse (1) have been fulfilled. It’s proper to consider elements of the chapter against perpetrators of corruption, professional/office of the perpetrator should be considered.